The Effect of Playing Methods on Increasing Physical Fitness of Futsal Players at Abhiseva Branch Club, Bengkulu City - Akbar, Muhamat; Sumantri, Ajis; Asnawati, Asnawati (UNIVED Press, Universitas Dehasen Bengkulu, 2025)
This study aims to determine the effect of playing methods on improving the physical fitness of futsal players at the Abhiseva branch club in Bengkulu City. This type of research is experimental research with the research method used is the Treatment by Level Design where the independent variable (X) is the playing method while the dependent variable (Y) is physical fitness. The number of samples is 20 students. The results of the study showed an increase in Physical Fitness values between the initial test (Pre-Test) and the final test (Post-Test) that had been carried out. This can be seen where the average value was 11.00 in the initial test and after being given the playing method treatment there was an increase in the average value of 16.00. In addition to the increase in the average value of the final test (Post-Test), it is also seen in the analysis of data descriptions, where in the initial test there were no samples that obtained a Physical Fitness Level value obtained as many as 3 people (15%) with a very poor classification, as many as 15 people (75%) with a poor classification, as many as 2 people (10%) with a moderate classification, and no players with good and very good classifications. Meanwhile, in the final test (Post-Test) there was an increase in scores, where there was no classification of very poor, in the poor category there were 2 people (10%), as many as 15 people (75%) with moderate classification, as many as 3 people (15%) with Good classification and none had reached the classification of very good.